Change in the Activity of Acidic and Alkaline Phosphatases in Immunocompetent Organs -a Criterion for Evaluating the Effectiveness of Immunobiological Preparations - O. V. Yurieva; V. I. Dubrovina; A. V. Korneva; T. P. Starovoitova; T. A. Ivanova; V. B. Nikolaev; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2017)
Dynamics of acidic and alkaline phosphatase activities was examined in thymus and spleen of laboratory mice immunized by cell wall preparations of Francisella tularensis of different subspecies. Cell wall preparations of two subspecies: F. tularensis subsp. mediaasiatica А-61(385) and F. tularensis subsp. novicida В-399 A-Cole (386) stimulated the rise of acidic and alkaline phosphatase activities in earlier time (7 days) after immunization than the others. It was correlated with their protective activity. On the basis of the results it is concluded that the studying of the acidic and alkaline phosphatase activities in immunocompetent organs can serve as one of the criteria for evaluation of efficiency of immunobiological preparations.